Active surveillance: transperineal biopsies and evaluation of multi-parametric magnetic resonance imaging - Bhat, Zubair; Bhat, Arshad; Abbaraju, Jayasimha; Wani, Mudassir; Bhat, Tahir; Deen, Shameer (International Surgery Journal, 2019)
Background: Active surveillance has emerged as an acceptable choice for low-risk prostate cancer patients and is defined as a treatment strategy of close monitoring through PSA, digital rectal examination, imaging and prostate biopsy, with conversion to curative treatment if progression occurs. An ideal tool for risk-stratification would detect aggressive cancers and exclude such men from taking up active surveillance in the first place. Methods: We retrospectively reviewed patients who underwent transperineal template biopsies from January 2016 till December 2018. All the patients had been classified as low grade prostate cancer after conventional trans-rectal ultrasound guided biopsy and enrolled in AS after discussion in hospital MDM. As per NICE guidelines all patients underwent multi-parametric magnetic resonance imaging (MRI). All suspicious lesions were assigned a PIRAD score; this was followed by Trans-perineal prostate biopsy. 142 patients were on active surveillance and underwent mapping transperineal template biopsies and cognitive target biopsies. 130 of them had multi-parametric MRI prior to the biopsies. Results: In 52% of cases the histology was upgraded. In 34 (24%) the cancer was upgraded to Gleason 3+4 and 39 (28%) it was upgraded to scores higher than Gleason 3+4. Only 64 (45%) patients continued on active surveillance post-template biopsies due to significant upgrading of histology. Conclusions: We advocate combination of MRI and an early transperineal template guided prostatic biopsies for intermediate risk prostate cancer, multiple core involvement, higher PIRAD grades and suspicious prostate on digital rectal examination in order to re-stage the initial disease and provide better safety for this cohort of patients.